A preliminary study on fraud prevention and detection at the state and local government entities in Malaysia - Ghazali, Mohamad Zulkurnai; Rahim, Mohd Syahrir; Ali, Azharudin; Abidin, Shamharir (Elsevier Ltd., 2014)
This study examines the occurrence of fraud and identifies the prevention programs in place at the State and Local Government entities in Malaysia. Issues related to fraud are of interest due to the frequent coverage by the media which has affected public confidence.The findings suggest that fraud is a significant problem, and the main causes of fraud are poor management practices and economic pressure. Interestingly, the study finds that, in most cases, management did not take firm action against the culprits when they were caught and found guilty. Most fraud incidents were discovered through the internal audit review, employee notification and accidental discovery.The findings also reveal that most of these entities did not have effective policies and procedures for dealing with fraud.